Designing an optimal stope layout for underground mining based on a heuristic algorithm - Sandanayake, D.; Topal, Erkan; Asad, M. (China University of Mining and Technology, 2015)
An optimal layout or three-dimensional spatial distribution of stopes guarantees the maximum profitability over life span of an underground mining operation. Thus, stope optimization is one of the key areas in underground mine planning practice. However, the computational complexity in developing an optimal stope layout has been a reason for limited availability of the algorithms offering solution to this problem. This article shares a new and efficient heuristic algorithm that considers a three-dimensional ore body model as an input, maximizes the economic value, and satisfies the physical mining and geotechnical constraints for generating an optimal stope layout. An implementation at a copper deposit demonstrates the applicability and robustness of the algorithm. A parallel processing based modification improving the performance of the original algorithm in terms of enormous computational time saving is also presented.